Modelling the association between weight status and social deprivation in English school children: Can physical activity and fitness affect the relationship?. (1st November 2016) - Nevill, Alan M.; Duncan, Michael J.; Lahart, Ian; Sandercock, Gavin
Abstract: Background : The association between being overweight/obese and deprivation is a serious concern in English schoolchildren. Aim : To model this association incorporating known confounders and to discover whether physical fitness and physical activity may reduce or eliminate this association. Subjects and methods : Cross-sectional data were collected between 2007–2009, from 8053 10–16 year old children from the East-of-England Healthy Heart Study. Weight status was assessed using waist circumference (cm) and body mass (kg). Deprivation was measured using the Index of Multiple Deprivation (IMD). Confounding variables used in the proportional, allometric models were hip circumference, stature, age and sex. Children's fitness levels were assessed using predicted VO2 max (20-metre shuttle-run test) and physical activity was estimated using the Physical Activity Questionnaire for Adolescents or Children. Results : A strong association was found between both waist circumference and body mass and the IMD. These associations persisted after controlling for all confounding variables. When the children's physical activity and fitness levels were added to the models, the association was either greatly reduced or, in the case of body mass, absent. Conclusions : To reduce deprivation inequalities in children's weight-status, health practitioners should focus on increasing physical fitness via physical activity in areas of greater deprivation.